Diacerein-loaded surface modified iron oxide microparticles (SMIOMPs): an emerging magnetic system for management of osteoarthritis via intra-articular injection - Ali, Nouran Abdelmageed; Morsi, Nadia M.; Badr-Eldin, Shaimaa M.; Shamma, Rehab N. (Frontiers in Bioengineering and Biotechnology, 2024)
Recently, considerable interest in utilizing intra-articular (IA) injections for managing osteoarthritis (OA) has been raised. In this study, IA injectable surface modified iron oxide microparticles (SMIOMPs) loaded with Diacerein (DCN) were developed. The effects of formulation parameters on particle size, entrapment efficiency, and zeta potential were explored using factorial design. The selected optimized system included 2M FeCL3 and 1% chitosan as a surface modifier achieved high drug entrapment of 85.25% with a PS of 1.54 µm and sustained DCN release. Morphological examination of the optimized formulation revealed spherical particles with chitosan coat. Differential scanning calorimetry and Fourier-transform infrared spectroscopy results indicated the absence of undesired interactions between DCN and the used components. No significant change in the measured parameters was observed following sterilization of the optimized formulation using gamma radiation.In vivo assessment of the optimized system in rats with induced arthritis revealed superior performance in reducing cartilage inflammation and degradation. Plasma levels of tumor necrosis factor α and Interleukin-1 beta, as well as knee diameter, were significantly reduced in the treated groups compared to the untreated ones. Overall, the results suggest that the proposed DCN-loaded SMIOMPs represent a promising advancement in the arena of cartilage regeneration.